Chemistry of Diterpenes from Dodonaea Species - Matan, Ahmed (Curtin University, 2024)
Native Western Australian plants are a prolific source of natural products. The largely unstudied Dodonaea genus is an abundant source of diterpenes with interesting chemistry that can be used as a feedstock for drug discovery. This thesis discussed the isolation of diterpenes from D. ceratocarpa, D. inaequifolia, and D. viscosa subsp. angustissima. Exploration of the chemistry of these diterpenes accessed the bioactive compound PL3 and several other anti-parasitic compounds.